New species of the genus Tabanus linnaeus, 1758 (diptera: tabanidae) from Malaysia - Al-Talafha H.,; Yaakop S.,; Nurul Fatihah A.L.,; Idris A.B., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Tabanids are true flies, with medical and veterinary importance. In the current report, a new species; Tabanus zuhairi sp. nov. is described. Main taxonomic characters including antennae, frons, and palpi are illustrated. The new species is recognized based on the cross-band of the wing and shiny subcallus.